Constraining dictatorship : from personalized rule to institutionalized regimes - Meng, Anne 1987- (Political economy of institutions and decisions, 2020)
How do some dictatorships become institutionalized ruled-based systems, while others remain heavily personalist? Once implemented, do executive constraints actually play an effective role in promoting autocratic stability? To understand patterns of regime institutionalization, this book studies the emergence of constitutional term limits and succession procedures, as well as elite power-sharing within presidential cabinets. Anne Meng argues that institutions credibly constrain leaders only when they change the underlying distribution of power between leaders and elites by providing elites with access to the state. She also shows that initially weak leaders who institutionalize are less likely to face coup attempts and are able to remain in office for longer periods than weak leaders who do not. Drawing on an original time-series dataset of 46 countries in Sub-Saharan Africa from 1960 to 2010, formal theory, and case studies, this book ultimately illustrates how some dictatorships evolve from personalist strongman rule to institutionalized regimes.